Persepsi Masyarakat Terhadap Penggunaan Pedestrian Sebagai Ruang Publik (Studi Kasus : Area Pedestrian Jalan Pelabuhan Ulee Lheue) - Nanda Yuli Elfizar; Zya Dyena Meutia; Fahmi Aulia; Zardan Araby (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Public open space is a place that can fulfill a need that is functional. Public open space in the Ulee Lheue considered still lacks that this area requires special attention to well ordered. Researchers conducted research in the Ulee Lheue because this region is particularly at the area of pedestrian roads Ulee Lheue port there are still many obstacles. An area used as a pedestrian has been used for a trade for small street vendors located in that area.